BENEFITS OF DAILY READING - Ibrohim Mahmudov; Rahmatova E’zoza (TADQIQOTLAR, 2025)
Annotation: This article explores the extensive benefits of daily reading, the methods  to  build  and  sustain  a  reading  habit,  and  the  profound  impact  it  has  on personal, professional, and intellectual growth. It provides insights into how reading shapes individuals and its importance in an ever-changing world.